Knowledge, attitude, and practices on disposal methods of expired and unused medicines among students in public academic institutions in Lusaka, Zambia - Kampamba, Martin; Cheela, Trevor; Hikaambo, Christabel Nang’andu; Mudenda, Steward; Saini, Kennedy; Chabalenge, Billy (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Unsafe disposal of unused and expired household medicines is a public health problem and mostly occur because of a lack of knowledge towards suitable medicine disposal methods. Thus, we aimed to assess the knowledge, attitude, and practices on the disposal methods of unused and expired medicines among students in public academic institutions in Lusaka, Zambia. Methods: This was a cross-sectional study in which 385 students from three higher learning academic institutions were interviewed face to face using a structured questionnaire from 10th May to 24th June 2019. The cleaned data was then transferred to statistical package for social science (SPSS) version 25.0 for analysis. Results: The mean age of the participants was 23 (SD±2.9). Out of the 385 participants, 215 (55.8%) did not know much about medical waste and 345 (89.6%) of them did not have any previous information regarding proper and safe disposal of unused and expired medicine. However, 351 (91.4%) of the participants appropriately responded that unsafe disposal of unused and expired medicine poses a threat to human health and can harm the environment. Throwing unused and expired medicine in household garbage/bin was the most frequently used disposal practice followed by flushing them in toilet/sink as responded by 231 (60.0%) and 128 (33.3%) of participants respectively. Only 17 (4.42%) reported returning unused and expired medicines to the nearest pharmacy. Conclusions: The majority of the study participants used unsafe methods to dispose of unused and expired medicine. However, most of the participants acknowledged that unsafe disposal of unused and expired medicines is a public health problem and proposed the need to introduce drug take-back programs in the communities.